Validity evidence of the Depression, Anxiety, and Stress Scale in Brazilian nursing workers - de Oliveira, Samuel Andrade; José Santin Júnior, Lacir; Fernanda Larios Fracarolli, Isabela; Martins, Bianca Gonzalez [UNESP]; Alvares Duarte Bonini Campos, Juliana [UNESP]; Helena Palucci Marziale, Maria; Deodato, Sergio Joaquim; Ludmilla Rossi Rocha, Fernanda (Acta Paulista de Enfermagem, 2025)
Objectives: To investigate the validity evidence of the Depression, Anxiety, and Stress Scale (DASS-21) and to analyze the prevalence of depression, anxiety, and stress symptoms in a sample of Brazilian nursing workers. Methods: This was a cross-sectional study with non-probability convenience sampling. A total of 4053 Brazilian nursing workers participated in the study. The psychometric properties of DASS-21 were assessed by analysis of the validity based on the internal structure (factorial, convergent, and discriminant construct validity, invariance of the factorial model, and reliability); relationships with external measures (positive and negative convergent validity of the depression, anxiety, and stress factors with the emotional impairment, job satisfaction, and individual and occupational variables); and response process of the items (analysis of the differential item functioning in distinct subgroups). Data reliability was certified by estimating the ordinal alpha coefficient and the composite reliability. The prevalence of depression, anxiety, and stress symptoms was estimated based on recommendations from the original authors of DASS-21. Results: During validation of the internal structure, the confirmatory factor analysis showed that the fit of the sample to the original DASS-21 model was adequate and the strong measurement invariance of the model was confirmed in different groups. Analysis based on external measures showed that the depression, anxiety, and stress factors had positive and moderate-strong correlations with the emotional impairment domain and negative and moderate correlations with the job satisfaction construct. Analysis of the pattern of response to items confirmed the uniformity and stability of the instrument for the sample. Regarding symptoms, the high prevalence of extremely severe levels of depression, anxiety, and stress was highlighted among participants. Conclusion: DASS-21 presented adequate validity and reliability to assess depression, anxiety, and stress symptoms among Brazilian nursing workers.
Evidencias de validez de la Depression, Anxiety and Stress Scale entre trabajadores de enfermería brasileños
Evidências de validade da Depression, Anxiety and Stress Scale entre trabalhadores de enfermagem brasileiros
Keywords: Anxiety; Brazil; Depression; Nurse practitioners; Occupational health; Psychiatric Status Rating Scales; psychological; Psychometrics; Stress; Surveys and questionnaires